A shift in a hake (Merluccius merluccius) population of the NW Mediterranean inducedby a combined effect of climate and fishery harvesting ... - Hidalgo, Manuel; Rouyer, Tristan; Massutí, Enric; Moranta, Joan; Guijarro, Beatriz; Stenseth, Nils Christian (ASC 2009 - Theme session F, 2024)
No abstracts are to be cited without prior reference to the author.Climate and fisheries are often interacting with each other and producing complex synergic effects on the population dynamics of marine species. The drastic change in the climatic conditions in the North Atlantic (NA) in the early eighties triggered changes in local weather and hydrographical conditions in the Mediterranean Sea. In the other hand, the long term fishery harvesting on the stock of European hake (Merluccius merluccius) off the Balearic Islands (BA, NW Mediterranean) changed the properties of the population and its structure in the early eighties, which could have triggered a different response to the environmental variability. Using time series analysis (on the environmental and hake CPUE time series) and a population simulation model, we examine the hypothesis that these processes are linked and, in turn, a combined effect of fishery harvesting and environmental changes in the NA induced an ecological shift in the hake ...